2020
DOI: 10.3390/molecules25204746
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue “Flavonoids and Their Disease Prevention and Treatment Potential”: Recent Advances and Future Perspectives

Abstract: In recent years, the interest in flavonoids as dietary bioactives to prevent human diseases, as well as their candidacy as pharmaceutical leads, has exponentially expanded [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 34 publications
1
30
0
1
Order By: Relevance
“…Approximately 6000 flavonoid compounds are estimated to be distributed in different fruits, vegetables, herbs, and plants [ 47 ]. Flavonoids offer diverse health benefits against chronic diseases, including cardiovascular disease, kidney disease, cancer, diabetes, obesity, and hepatic disease, which lead to increased mortality and morbidity [ 48 , 49 , 50 ]. Because of their potent antioxidant and anti-inflammatory activities, they can modify various enzymes and signaling molecules that are responsible for disease prognosis [ 51 ].…”
Section: Polyphenols In Managing Muscle Atrophy and Muscle Healthmentioning
confidence: 99%
“…Approximately 6000 flavonoid compounds are estimated to be distributed in different fruits, vegetables, herbs, and plants [ 47 ]. Flavonoids offer diverse health benefits against chronic diseases, including cardiovascular disease, kidney disease, cancer, diabetes, obesity, and hepatic disease, which lead to increased mortality and morbidity [ 48 , 49 , 50 ]. Because of their potent antioxidant and anti-inflammatory activities, they can modify various enzymes and signaling molecules that are responsible for disease prognosis [ 51 ].…”
Section: Polyphenols In Managing Muscle Atrophy and Muscle Healthmentioning
confidence: 99%
“…Numerous researchers have demonstrated that anticarcinogenic effects of polyphenols are assigned to several mechanisms, including the induction of apoptosis, regulation of various cell signaling pathways, regulation of the cell cycle, DNA repair, and activation of the receptors [ 195 , 196 ]. Flavonoids are known to activate the Keap1/Nrf2/ARE pathway and contribute to cytoprotection in normal cells [ 197 ]; however, some flavonoids such as flavones, luteolin, apigenin, and chrysin are shown to inhibit Keap1/Nrf2/ARE and are proapoptotic in cancer cells [ 198 ].…”
Section: Dietary Antioxidants As Anticancer Agentsmentioning
confidence: 99%
“…Chrysin, a flavone [ 5 ], is one of the potential polyphenols widely distributed in plant-based foods [ 6 ]. A plethora of evidence supports the health benefits of polyphenolics in managing physiological functions and the prevention of chronic oxidative stress-triggered disease conditions such as cancers, diabetes, and cardiovascular as well as neurodegenerative disorders [ 7 ]. Chrysin, a bioactive phytoconstituent, has a broad range of pharmacological spectra showing anti-inflammatory, anti-oxidant, anti-aging, anti-cancer, and cardioprotective properties [ 8 ].…”
Section: Introductionmentioning
confidence: 99%